Levofloxacin Preventive Treatment in Children Exposed to MDR Tuberculosis - Hesseling, Anneke C.; Purchase, Susan E.; Martinson, Neil A.; Fairlie, Lee; Schaaf, H. Simon; Brigden, Joanna; Staples, Suzanne; Gibb, Diana M.; Garcia-Prats, Anthony; Conradie, Francesca; McGowan, Charlotte; Layton, Charlotte; et al. (The New England journal of medicine, 2024)
In this randomized, controlled trial involving children with household exposure to multidrug-resistant tuberculosis, levofloxacin led to a lower incidence of tuberculosis than placebo, but the difference was not significant.